Pergeseran Komposisi Gulma, Pertumbuhan dan Hasil Jagung Manis dengan Aplikasi Herbisida Campuran - Bilman Wilman Simanihuruk (Rawa Sains: Jurnal Sains STIPER Amuntai, 2016)
The decline in sweet corn production needs to be done to increase production through the use of dry land, both those that have become agricultural land and those that have not been used. In the business of using dry land it is often found that problems such as productivity decline rapidly, low soil fertility and many types of weeds. Especially wide, narrow weed leaves and woody shrubs. Experiment using Split Plot Design. The main plot is the dose of glyphosate consists of 3 levels, namely g1= 1,5 l/ha, g2 = 2 l/ha, dan g3 = 2,5 l/ha. The subplot is a 2,4-D dose consisting of 3 levels, namely d1 = 0,5 l/ha, d2 = 1 l/ha, d3= 1,5 l/ha. The use of a herbicide mixture of glyphosate and 2,4-D was able to shift the weed composition with a value of C of 68.75% at 2 days before harvest. Glyphosate herbicide dose of 1.5 l/ha was able to produce plant growth rates of 2.23607813 g cm-2 days-1, and the weight of the selling cob was 129,408 g